2022-RA-1000-ESGO Review of adherence to NICE guidance on lynch syndrome testing for patients diagnosed with endometrial cancer in BHSCT. (20th October 2022) - Ralston, Charlotte; Birkett, Philip; McCluggage, Glenn; Dobbs, Stephen; Nagar, Hans; Craig, Elaine; McComiskey, Mark; Harley, Ian
Abstract : Introduction/Background: Lynch syndrome is an inherited condition increasing the likelihood of developing certain cancers. Routine testing for patients diagnosed with colorectal cancers has been recommended by NICE guidance since February 2017 and in October 2020 this guidance was updated to recommend testing for patients diagnosed with endometrial cancer. Methodology: A retrospective analysis of patients diagnosed with endometrial cancer between January 2020 and November 2021 reviewed adherence to the new guidelines and identify patients missed for follow up. We analysed histopathology and medical records for all patients with a new diagnosis in this period and collected data on patient demographics, immunohistochemistry (IHC) and pathological diagnosis. Results: 113 patients were diagnosed with endometrial cancer, 48 before and 65 after the update. In total 19 were diagnosed with mismatch repair (MMR) abnormalities on immunohistochemistry and 7 referred on for Germline testing. Pre-update, 6 of the 48 patients (12.5%) did not have MMR testing following diagnosis and 40% of patients with MMR abnormality went on to have Germline testing. Post-update, only 1 of the 65 patients (1.5%) were not tested for MMR abnormalities, with 30% of patients with MMR abnormalities undergoing Germline testing. Conclusion: There was a clear improvement in performance of MMR testing after updated guidance but 100% was not reached. A letter was sent to the responsible pathologist for reflex testing of all endometrial cancer patients with MMR IHC abnormalities, preferably at diagnostic biopsy. For those patients with MMR deficiency on IHC who have not been referred for Germline testing for Lynch syndrome; a notification has been sent to the responsible gynaecologist. It was also noted that family history was not included on all histopathology request forms. As this this is a significant factor risk stratification for Lynch syndrome, we would recommend this being included on requests for any endometrial samples.